Last Mile Access to Enriched Children's Complementary Food: Mitigating Malnutrition in Kenya - Muthuuri Pamela; Kassim Joseph; Richard Patrick; Mwarania Florence (Frontiers Media S.A., 2021)
Commercial complementary foods are not accessible at the last mile of delivery, despite a veritable stunted growth explosion in Kenya. A Mile for the Brain aims to reduce child malnutrition by solving the pervasive distribution bottlenecks and prohibitive pricing challenges. This paper presents the systematized measurement for change process. We focus on the selection of off-the-shelf complementary foods, training of women entrepreneurs responsible for commercializing these complementary foods, coaching given to mothers on appropriate feeding education, and lastly the learning cycle revolving around feeding mothers, entrepreneurs for the Mile for the Brain social enterprise itself. We highlight the real-life challenges involved in this process in the context of adversity and constrained resources. The results, findings, and policy implications of this study will be reported elsewhere.